2015
DOI: 10.1093/jac/dkv123
|View full text |Cite
|
Sign up to set email alerts
|

Can therapeutic drug monitoring optimize exposure to piperacillin in febrile neutropenic patients with haematological malignancies? A randomized controlled trial

Abstract: Conventional doses of piperacillin/tazobactam may not offer adequate piperacillin exposure in febrile neutropenic patients. TDM provides useful feedback of dosing adequacy to guide dose optimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 24 publications
3
68
1
Order By: Relevance
“…In such patients, extended infusion over half of the dosing interval may significantly improve the probability of target attainment without increasing the total dose administered, thus minimizing the apparent toxicity concerns (15,39). Clinical studies have reported increased percentage of fT ϾMIC with prolonged infusion for cefepime (39,40) and other ␤-lactam antibiotics (15,41). Current PK/PD understanding is that improved exposure can potentially translate into improved clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In such patients, extended infusion over half of the dosing interval may significantly improve the probability of target attainment without increasing the total dose administered, thus minimizing the apparent toxicity concerns (15,39). Clinical studies have reported increased percentage of fT ϾMIC with prolonged infusion for cefepime (39,40) and other ␤-lactam antibiotics (15,41). Current PK/PD understanding is that improved exposure can potentially translate into improved clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we conducted a randomized controlled study to test the utility of piperacillin TDM in febrile neutropenic patients (6). We found that TDM was able to increase the success rate of target attainment from a baseline of 19% to 73%, in contrast to a decrease from 25% to 7% in the control group.…”
mentioning
confidence: 98%
“…Immuno assays are usually an attractive choice as they do not require special expertise, equipment or significant resources. Yet, immunoassays which have provided such advantages for antibiotics as aminoglycosides, do not exist for β-lactams and attempts for the establishment of such techniques have been difficult [6,55]. Therefore, with the current limitations the use of immunoassays for antibiotics' TDM is not considered as a priority for further development and efforts have been directed to explore other alternatives such as the use of chromatographic techniques.…”
Section: Overview Of Published Analytical Methods Optimized For Theramentioning
confidence: 99%
“…Even after treatment with oseltamivir, all patients died from respiratory tract infection and multiple organs failure [5]. Recent studies show that the dosing regimen of two β-lactam antibiotics (cefepime and piperacillin), prescribed for febrile neutropenic patients with hematological malignancies, requires adjustment [6,7] especially in the presence of organ dysfunction [8]. The need for dose adjustment is mainly due to the fact that the pathophysiological changes encountered in ICU patients substantially affect the pharmacokinetic profile of a drug predisposing the patients to toxic or sub-therapeutic concentrations, when standard doses are applied.…”
Section: Introductionmentioning
confidence: 99%